Investigation of Optimal Coupling Velocities of the Sample and Sheath Flows for Hydrodynamic Focusing - Dingpeng Huang; Hangzhou Wang; Xiaoping Wang; Kan Guo; Zhuoli Yuan; Jiawang Chen; Ying Chen (Journal of Marine Science and Engineering, 2020)
Focusing performance is a major concern for systems based on hydrodynamic focusing. In this study, the hydrodynamic focusing subsystem of a microscopic imaging system was analysed and modelled. The theoretical model was used to analyse the velocity and distribution range of sample particles in the focused sample flow in the micro-channel of the hydrodynamic focusing subsystem, when the velocities of the sample and sheath flows were varied. The results were used to optimise the coupling velocities of the sample and sheath flows for the microscopic imaging system, to keep working efficiency and image quality of the system simultaneously. An independent experiment was then conducted for verification, and the results agreed well with the theoretical investigation. The results of this study provide a general framework for adjusting the sample and sheath flow velocities to optimise the hydrodynamic focusing performance.